2018
DOI: 10.1101/420554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Over-expression of Hsp83 in grossly depletedhsrωlncRNA background causes synthetic lethality andl(2)glphenocopy inDrosophila

Abstract: We examined interactions between Hsp83 and hsrω lncRNAs in hsrω 66 Hsp90GFP homozygotes, which almost completely lack hsrω lncRNAs but over-express Hsp83. All +/+; hsrω 66 Hsp90GFP progeny died before third instar. Rare Sp/CyO; hsrω 66 Hsp90GFP reached third instar stage but phenocopied l(2)gl mutants, dying after prolonged larval life, becoming progressively bulbous and transparent with enlarged brain. Additionally, ventral ganglia were elongated. However, hsrω 66 Hsp90GFP/TM6B heterozygotes, carrying +/+ or … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 123 publications
(204 reference statements)
0
5
0
Order By: Relevance
“…The upregulated groups of genes (Table ) in sev‐GAL4 > UAS‐Ras1 V12 hsrω‐RNAi pupae included, among many others, those associated with stress responses, cell and tissue death pathways, autophagy, toll signaling, innate immune system, and so forth. Some of these seem to be primarily due to activated Ras or altered hsrω expression since the Ras/MAPK pathway is known to regulate immune response while the hsrω transcripts have roles in stress responses, cell death, and several other pathways . However, beside the predicted upregulation of G‐protein coupled signal transduction pathway following ectopic expression of activated Ras, a significant increase in expression of several JNK pathway genes was also noted (Tables and ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The upregulated groups of genes (Table ) in sev‐GAL4 > UAS‐Ras1 V12 hsrω‐RNAi pupae included, among many others, those associated with stress responses, cell and tissue death pathways, autophagy, toll signaling, innate immune system, and so forth. Some of these seem to be primarily due to activated Ras or altered hsrω expression since the Ras/MAPK pathway is known to regulate immune response while the hsrω transcripts have roles in stress responses, cell death, and several other pathways . However, beside the predicted upregulation of G‐protein coupled signal transduction pathway following ectopic expression of activated Ras, a significant increase in expression of several JNK pathway genes was also noted (Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in our and other labs have shown that the hsrω lncRNA gene in Drosophila melanogaster regulates many cellular regulatory pathways through diverse mechanisms, of which the modulation of dynamics of heterogeneous nuclear RNA binding proteins (hnRNPs) and certain other RNA binding proteins seems to be a major component . We had earlier found a genetic interaction between Hsp83, Ras signaling pathways and the hsrω lncRNAs .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The up-regulated groups of genes (Table 2) in sev-GAL4>UAS-Ras1 V12 hsrω-RNAi pupae included, among many others, those associated with stress responses, cell and tissue death pathways, autophagy, toll signaling, innate immune system etc. Some of these seem to be primarily due to activated Ras or altered hsrω expression since the Ras/MAPK pathway is known to regulate immune response (Ragab et al, 2011;Hauling et al, 2014) while the hsrω transcripts have roles in stress responses, cell death and several other pathways (Mallik and Lakhotia, 2009a;Lakhotia, 2011;Lakhotia, 2016;Ray et al, 2019a;Ray et al, 2019b). However, beside the predicted up-regulation of G-protein coupled signal transduction pathway following ectopic expression of activated Ras, a significant increase in expression of several JNK pathway genes was also noted (Tables 2 and 3).…”
Section: Transcriptome Analysis Of Early Dying Pupae Showed Down Regumentioning
confidence: 99%